Comparative analysis of COMET, FISH, and TUNNEL methods for assessing DNA damage in plants under abiotic and biotic stresses - Turarbekova, Zhibek; Iksat, N.; Madirov, A.; Tuyakbayeva, A.; Masalimov, Z. (Fundamental and Experimental Biology, 2025)
Research aimed at studying plant DNA damage caused by various stress factors is an important area of modern molecular biology and genetics. In recent decades, there has been an intensive development of methods that make it possible to analyze in detail the molecular reactions of plants to abiotic and biotic stresses, which significantly deepens our understanding of the mechanisms of plant adaptation to adverse conditions. One of the key aspects of such studies is the assessment of damage to genetic material, which plays an important role in disrupting the normal functioning of plant cells and tissues. Special attention is paid to the combined effects of stress factors such as high fever and viral infections, such as Tobacco bushy stunt virus (TBSV) infection, which can significantly disrupt DNA integrity and disrupt normal cellular processes. This, in turn, can lead to changes in the activity of key genes, DNA repair, as well as effects on the physiological and morphological characteristics of plants. In this article, we examined three methods that are actively used to assess DNA damage under combined stress conditions: COMET, TUNNEL and FISH. These methods allow for a comprehensive analysis of DNA damage, as well as to investigate their relationship to physiological and cellular changes in plants exposed to viral and temperature stress. The purpose of this study is to explore the prospects of using COMET, FISH and TUNNEL assay methods to assess the level of damage in plant DNA under the influence of abiotic and biotic stress. The research is aimed at analyzing their effectiveness, as well as identifying advantages and limitations when working with plant objects.